Dispersion analysis of nanofillers and its relationship to the properties of the nanocomposites. (2021) - George, Gibin; Dev, Amal P.; Asok, N. Nikhil; Anoop, M.S.; Anandhan, S.
Abstract: The dispersion and distribution characteristics of the reinforcements are the key reasons that influence the mechanical properties of the nanocomposites. In this paper, the dispersion and distribution analysis of nanofillers in a representative polymer is performed and the results are correlated to the crystalline and mechanical properties of the nanocomposite. The nanocomposite used in the present study is Elvaloy®4924 (EVACO)/halloysite nanotubes (HNTs) composite. The dispersion of halloysite nanotubes in the EVACO matrix is recorded as aluminum elemental maps obtained from energy dispersive spectroscopy (EDS). The dispersion and distribution of fillers in the composite are quantified using an image processing technique and it is correlated to the crystalline and tensile properties of the composites. The better dispersion and distribution of HNTs at 1wt.% filler loading resulted in a remarkable improvement in the crystallinity of the composite, which is measured by X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The tensile strength was highest for composites loaded with 1 wt.% filler, and the strength decayed as the loading was further increased. Agglomeration of halloysite nanotubes and polymer-filler debonding was the major reason behind the reduction in tensile strength with filler loading, as observed in the scanning electron micrographs of the fractured surfaces.